Effect of external application of Rhubarb at Shenque (CV8) in the treatment of abdominal distension in patients with chronic obstructive pulmonary disease with syndrome of phlegm-heat obstructing lung (大黄外敷神阙穴治疗慢性阻塞性肺疾病痰热壅肺型患者腹胀的效果) - JIANG Xiaoqong (江晓琼); LONG Wen (龙文) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the effect of external application of Rhubarb at Shenque (CV8) in the treatment of abdominal distension in patients with chronic obstructive pulmonary disease(COPD)with syndrome of phlegm-heat obstructing lung. Methods Totally 60 COPD (phlegm-heat obstructing lung)patients with abdominal distension were divided into control group and treatment group, with 30 cases in each group. The control group received abdominal massage, and the treatment group was given effect of external application of Rhubarb at Shenque (CV8) combined with abdominal massage. The degree of improvement in abdominal distension was evaluated after intervention. Results A greater degree of improvement in abdominal distension was found in the treatment group than that in the control group(P＜0. 05). Conclusion The external application of Rhubarb at Shenque (CV8) is effective to relieve abdominal distension in patients with COPD with syndrome of phlegm-heat obstructing lung. (目的 探讨大黄外敷神阙穴治疗慢性阻塞性肺疾病(COPD)痰热壅肺型患者腹胀的效果。方法 60例COPD痰热壅肺型伴腹胀患者分为对照组和治疗组, 各30例。对照组采用腹部按摩治疗, 治疗组在对照组的基础上采用大黄外敷神阙穴治疗。评估2组腹胀改善情况。结果 治疗组腹胀缓解程度优于对照组(P＜0. 05)。结论 大黄外敷神阙穴能够有效改善COPD痰热壅肺型患者腹胀程度。)